2001
DOI: 10.1108/02683940110385749
|View full text |Cite
|
Sign up to set email alerts
|

Violating psychological contract terms amongst Maltese public service employees: occurrence and relationships

Abstract: The psychological contract is the construct through which one attempts to explain the quality of the employment relationship from the point of view of each of the contract party with regards to obligations and inducements and can be employed to explain organizational change dynamics. Failing to provide promised obligations is termed as violation. This study examined the occurrence of contract violation amongst 132 Maltese public service employees at a time when radical changes in practices were being proposed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
1
21
0
9
Order By: Relevance
“…Based on this reasoning as well as empirical support from the organizational literature (e.g., Cassar 2001;Johnson and O'Leary-Kelly 2003), we hypothesize that:…”
Section: Mediating Relationshipsmentioning
confidence: 95%
“…Based on this reasoning as well as empirical support from the organizational literature (e.g., Cassar 2001;Johnson and O'Leary-Kelly 2003), we hypothesize that:…”
Section: Mediating Relationshipsmentioning
confidence: 95%
“…Coyle-Shapiro and Kessler (2002) confirmed these results concerning the norm of reciprocity in the English public sector, which is defined by Gouldner (1960) as a universal need to reciprocate after having received some benefits. Cassar (2001) found that psychological contract violation amongst Maltese public service employees was negatively associated with trust, commitment and job satisfaction. Guest and Conway (1998), who also studied psychological contracts in the English public sector; found that the reduction of trade union power could explain the perception of the increasing breach in the psychological contract in English public services.…”
Section: Psychological Contract In Public Organizationsmentioning
confidence: 95%
“…Sometimes, employees feel organizational mistreatment is too verse and further, they perceive more chances of same treatment, so they decide to leave organization and seek new venues for employment. Most of the research studies reported consistent results that psychological contract breach (PCB) tends to decrease employee's positive and proactive attitude towards organization, in fact, it is negatively influenced on employee behaviors including organizational commitment, job satisfaction and increases employee's intent to quit the job (Topa and Morales, 2005a, c;Coyle-Shapiro and Kessler, 2002;Guglielmi, 2003;Mc Donald and Makin, 2000;Cassar, 2001): P 1 : Perceptions of psychological contractbreach has a positive impact on intention to quit and negative impact on employees' commitment and job satisfaction. Figure 1 shows the conceptual model of this paper.…”
Section: Psychological Contract Breachmentioning
confidence: 99%